Knowledge sharing in projects: does employment arrangement matter?. Issue 2 (2nd March 2015) - Nesheim, Torstein; Smith, Janne
Abstract : Purpose: – The core of project management is the management of a temporary task, often with a high degree of uniqueness. The purpose of this paper is to address project management issues where another type of temporality also prevails; when external consultants on short-term contracts cooperate with the employees of the focal firm. The research question is: do external consultants and employees, working together on a project, engage in different or similar knowledge sharing behaviors? What are the impact of autonomous motivation, organizational support and trust on knowledge sharing? Design/methodology/approach: – The empirical setting of the study is subsea activities, which is part the oil and gas industry in Norway. The respondents are regular employees with a permanent contract and external consultants employed by a third party; which is the most common external work arrangement in the industry. The sample consists of employees of a focal firm, external consultants of the focal firm and external consultants identified by their employer (two firms). The survey was administered by e-mail to 323 possible respondents. Of these, 268 were from the focal firm (194 employees and 74 external consultants), and 55 from the two consulting companies. After four weeks of collecting data, 138 responses had been registered. This is a response rate of 43 percent. The response rates were similar in the three categories. The survey was designed using Qualtrics, an online survey software tool and was administered by e-mail in the winter of 2012. Findings: – The regression analysis found that there was no difference in knowledge sharing between employees and external consultants. Thus the empirical analysis supports the "project identity" hypothesis, rather than the "employment matters" hypothesis. Further, there were positive, significant impacts of autonomous motivation and perceived organizational support on knowledge sharing. The findings are similar across samples. R 2 is quite high in models B (0.447) and D (0.458), indicating that a large share of the variation in knowledge sharing is explained by the full model. Research limitations/implications: – Based on the empirical study here, the "employment arrangement" thesis was not supported. The authors believe, however, that combining the two types of temporality (work organization and employment arrangement) is a promising area of exploration and it is not given that further studies will provide similar empirical findings. Further research should explore under what conditions employment arrangements have an impact on knowledge sharing. The research may be extended along three dimensions. First, the study of knowledge sharing when employees and external consultants work together (on projects managed by the focal firm) should be extended to include other firms, other types of competence as well as economic sectors outside petroleum. Second, research on employment arrangements in projects, should consider project contexts that are different from the type emphasized here, such as development projects and projects that have a fundamental inter-organizational character characterized by dual responsibility. Third, a number of others issues, in addition to knowledge sharing, are relevant. Combining the two aspects of temporality may provide opportunities for exploring the impact of organizational context in the field of leadership studies. Practical implications: – Management should strive to increase autonomous motivation and provide organizational support for both employees and external consultants. It is possible to use external consultants without negative effects on the level of knowledge sharing. Managers should be aware of the challenges related to both types of temporality. Social implications: – Increased awareness of the relevance of both types of temporality in contemporary working life. Originality/value: – In previous research, project organization and temporary employment relations are two distinct areas. This is one of the first empirical studies that have analyzed both aspects of temporality. The paper contributes to the literature on antecedents of knowledge sharing in organizations, and suggest avenues for further research in this issue. Further, in addressing both types of temporality, a number of other research themes are suggested.